Assessing coach's personality and transformational leadership behavior among team and individual sports - Kassim, A. F. M.; Mazli, A.; Saufi, A.; Mansor, S. H. (The International Journal of Indian Psychology, 2021)
Leadership and personality have attributes that are essential to success in sports coaching. Personality is a combination of behaviour, emotion, motivation, and patterns of thought which defined an individual. Whilst, transformational leadership in a coach`s behaviour led to a change in individuals and social systems that will inspire and create value in the athletes. Therefore, this study aims to examine the coach personality and transformational leadership behaviour among the team and individual sports. One hundred and fifty-two (n=152) athletes from team sport (n=76) and individual sport (n=76), were participated in this study. The ages of the athletes were range from 18 to 25 years old, and all of them represented in the university games. A 27-item of Differentiated Transformational Leadership Inventory (DTLI) and a 32-item of Myers Briggs Type Indicator (MBTI) personality, were adopted and used for this study. Results revealed that the component of transformational leadership indicated a significant difference between individual and team sports athletes. Also, there were significant differences shown in the component of personality between the individual and team sports athletes, except for "introverted thinking". In conclusion, the personality of the coach may influence the role of the coach`s transformational leadership. Thus, playing a significant role in the growth of athletes, the coach`s personality and leadership attributes become the key factors for an athlete`s success and development.